The Classical Language of Architecture - John N. Summerson... (Editeur non renseigne, 1707)
Notice de démonstration issue d Open Library pour la thematique 'architecture'. Titre: 'The Classical Language of Architecture'. Auteur: John N. Summerson | Alan Powers. Premiere publication: 1707.
Métadonnées bibliographiques issues dOpen Library
Keywords: architecture; patrimoine; Patrimoine bâti